Metode Resitasi dan Peningkatan Hasil Belajar Siswa Pada Materi Menulis Teks Editorial di Masa Pandemi Covid 19 - Susi Alawiyah (Universitas Pancasakti Tegal, 2021)
This study aims to determine the effectiveness of the application of the recitation learning method on student learning outcomes at SMK Negeri 5 Tangerang Regency. The research method used is a classroom action research method. The population in this study was grade 12 SMK Negeri Tangerang Regency and the sample in this study was grade 12 TKJ1. The results of this study indicate that the recitation learning method is proven to be able to improve student learning outcomes, the percentage of student classical learning completeness increases from each cycle, namely cycle I of 42.31%, cycle II 80.38%, student learning activities in the first cycle have increased, namely cycle I of 63.46%, the second cycle was 73.90%. The ability of teacher'in the teaching and learning process in the classroom also increased where in the first cycle was in the sufficient category in the second cycle was categorized as good.